High-throughput screens using photo-highlighting discover BMP signaling in mitochondrial lipid oxidation - Yong Yu (Nature Portfolio, 2017)
High-throughput genetic screens in animals could benefit from an easy way to mark positive hits. Here the authors introduce photo-highlighting using a photoconvertible fluorescent protein, and in combination with stimulated Raman scattering (SRS) microscopy, define a role for BMP signaling in lipid metabolism in C. elegans.